How do general practitioners and specialists value their mutual communication? A survey - Voorn Theo B; Meyboom-de Jong Betty; Benneker Wim HGM; Kuiken Annegriet; Berendsen Annette J; Schuling Jan (BMC, 2009)
Abstract Background Communication between general practitioners (GPs) and specialists is important, if we want patients to receive the right type of care at the right moment. Most communication takes place through telephone contact, letters concerning information on patients more recently also by email, and joint postgraduate training. As much research has been aimed at the content of communication between GPs and specialists, we wished to address the procedural aspects of this communication. We addressed the following research question. How do GPs and specialists assess their mutual communication through telephone, letters and postgraduate courses? Methods A cross-sectional study was conducted among a random sample of 550 GPs and 533 specialists selected from the Netherlands Medical Address Book. The response rate was 47% GPs (n = 259) and 44% specialists (n = 232). Results Specialists qualify the GPs' telephone accessibility as poor; while GPs themselves do not. Specialists think poorly of the GPs' referral letter. Merely half of GPs feels their questions are addressed appropriately by the specialist, whereas specialists think this number is considerably higher. According to specialists, GPs often do not follow the advice given by them. GPs rate their compliance much higher. Less than a quarter of GPs feel the specialist's letter arrives on time. Specialists have a different perception of this. Both parties wish to receive feedback from one and other, while in practice they do so very little. Conclusion GPs and specialists disagree on several aspects of their communication. This impedes improvements. Both GP's accessibility by phone and time span to the specialist's report could be earmarked as performance indicators. GPs and specialists should discuss amongst themselves how best to compose a format for the referral letter and the specialist's report and how to go about exchanging mutual feedback.